Learning to complete the PhD thesis - Adham K.A.; Ha H.; Nor S.M.; Yazid Z. (Western Australian Institute for Educational Research Inc., 2024)
Research competencies are pertinent to academic researchers. Due to increasingly demanding work situations, academic researchers are forced to rapidly develop competencies in both qualitative and quantitative research. However, studies on how doctoral candidates develop competencies to complete their PhD theses are limited. This study, therefore, examines the types of learning method including the processes and drivers of learning among academics, who have successfully employed qualitative methodologies in their doctoral research. We used the perspectives of learning theories, doctoral education processes and network perspective as the studys conceptual framework. We employed a qualitative design comprising in-depth interviews with ten researchers in the field of management. The findings suggest that researchers learn qualitative methodologies through both formal and informal methods of learning. Self-study, guidance from supervisor and network support which are closely tied to ones own self-reflection contribute to the successful application of qualitative methodology in doctoral research. 2018, Western Australian Institute for Educational Research Inc.. All rights reserved.